Preemptive Treatment of Nausea and Vomiting of Pregnancy: Results of a Randomized Controlled Trial - Caroline Maltepe; Gideon Koren (Obstetrics and Gynecology International)
Objectives. To determine whether the initiation of treatment (preemptive treatment) before the symptoms of nausea and vomiting of pregnancy (NVP) versus when the symptoms begin can improve the outcome in patients at a high risk for recurrence of severe NVP. Study Design. Prospective, randomized controlled trial. Results. Preemptive therapy conferred a significant reduction in HG as compared to the previous pregnancy (P=0.047). In the preemptive arm, there were 2.5-fold fewer cases of moderate-severe cases of NVP than those in the control group (15.4% versus 39.13%) in the first 3 weeks of NVP (P=0.05). In the preemptive group, significantly more women had their NVP resolved before giving birth (78.2% versus 50%) (P<0.002). Conclusions. Preemptive treatment with antiemetics is superior to the treatment that starts only when the symptoms have already occurred in decreasing the risk of severe forms of NVP.